Efficacy Of Polydex And Anise Essential Oil In The Treatment Of Patients With Benign Vascular Lesions Of The Nasal Cavity (Eurasian Medical Research Periodical, 2024)
Benign vascular tumours of the mucous membrane of the nasal cavity and sinuses account for 10% of all hemangiomas of the head-neck region and 25% of all non-epithelial tumours of this region, being the most frequent among non-epithelial tumours and occupying the second place after epithelial neoplasms. The standard method of treatment of nasal cavity tumours involves their removal by surgery or with the use of modern technologies (laser destruction, sclerosing, etc.). However, in order for the patient to return to active life activity it is necessary to recover the postoperative field for a long time, which also causes considerable discomfort to the patient. In connection with this situation, as well as due to the lack of expected effects from traditional methods of treatment of postoperative patients there is a need to find more effective ways to combat postoperative effects. This work is devoted to the study of the effectiveness of polydex and essential oil of anise in this situation